2020
DOI: 10.1016/j.omtn.2019.11.009
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo RNAi-Mediated eIF3m Knockdown Affects Ribosome Biogenesis and Transcription but Has Limited Impact on mRNA-Specific Translation

Abstract: Translation is an essential biological process, and dysregulation is associated with a range of diseases including ribosomopathies, diabetes, and cancer. Here, we examine translation dysregulation in vivo using RNAi to knock down the m-subunit of the translation initiation factor eIF3 in the mouse liver. Transcriptome sequencing, ribosome profiling, whole proteome, and phosphoproteome analyses show that eIF3m deficiency leads to the transcriptional response and changes in cellular translation that yield few de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 65 publications
1
12
0
Order By: Relevance
“…30 -32 Through the analysis of genetic mutations in patients with cancer, we can tailor the treatment plan for each patient with cancer to maximize the curative effect, minimize the damage, and optimize the resources. 33 -36…”
Section: Precision Medicine and Tumor Gene Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 -32 Through the analysis of genetic mutations in patients with cancer, we can tailor the treatment plan for each patient with cancer to maximize the curative effect, minimize the damage, and optimize the resources. 33 -36…”
Section: Precision Medicine and Tumor Gene Detectionmentioning
confidence: 99%
“…[30][31][32] Through the analysis of genetic mutations in patients with cancer, we can tailor the treatment plan for each patient with cancer to maximize the curative effect, minimize the damage, and optimize the resources. [33][34][35][36] Next-Generation Sequencing and Precise Targeting Therapy for Tumors Next-generation sequencing, also known as large-scale parallel sequencing, can simultaneously sequence millions or even billions of DNA molecules, achieving the goal of large-scale, high-throughput sequencing. [37][38][39][40] This makes NGS a revolutionary progress following Sanger sequencing (firstgeneration sequencing).…”
Section: Precision Medicine and Tumor Gene Detectionmentioning
confidence: 99%
“…GO analysis showed that these genes are primarily involved in development and morphogenesis ( Figure 5C ). Several studies demonstrated that ∼60% RNAi efficiency of critical upstream genes was capable of altering the expression pattern of downstream genes by RNA-Seq analysis ( Brooks et al, 2011 ; Sun et al, 2018 ; Smekalova et al, 2020 ). Therefore, we further performed RNA-Seq on the hDMCs treated with BMP4 + control siRNA and BMP4 + SMAD4 siRNA, respectively, to test if the expression levels of these 586 genes involved in the BMP/pSMAD1/5/8 signaling cascade are altered by knockdown of SMAD4 .…”
Section: Resultsmentioning
confidence: 99%
“…The high efficacy of siRNA also decreases the possibility of off-target effects. Such setup provides a solid solution for proof-of-concept studies in the liver in vivo 52 , 62 . In order to achieve silencing of CCR2 mRNA, we compared previously published CCR2-targeting siRNA sequence with the best scored six siRNA in RAW264.7 cells (Supplementary Table 1 ).…”
Section: Resultsmentioning
confidence: 99%